Perspectives of different stakeholders about mental health care services provided by traditional healers in Ghana and the possibility of the integration of traditional medicine into mental health care - Yaro, Badimak Peter (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPhil)--Stellenbosch University, 2016.